Lack of University Education among Youth Deprived of Parental Care - Gurbanli, Nigar; Valiyeva, Elnaz; Mehraliyeva, Sakina (ADA University, 2022)
This capstone project reflects the problem of lack of university education among youth deprived of parental care. The project discusses the main causes which prevent those youth getting university education. Moreover, the study indicated that the main problems are related to the existence of financial difficulties, as well as psychological problems and traumas that the children face. Furthermore, it has revealed that lack of early childhood education and lack of skills and expertise in Orphanages, State Institutions and other Childcare Organizations is also among main problems. Subsequently, this paper suggests various policy options and provides evaluation of those solutions based on certain criteria such as efficiency, effectiveness, equity, feasibility and flexibility. Considering those criteria, the paper suggests that provision of special training programs for the development of skills and knowledge of teachers, caregivers and coordinators is one of the best options which will result further progress in children’s psychological and academic development. This project also proposed final recommendations based on the evaluation of problems and policy options.
Keywords: Education, Higher -- Azerbaijan.; Parental care.; Education, Higher -- Challenges.; Public and International Affairs